Finned zeolite catalysts - Dai, Heng; Shen, Yufeng; Yang, Taimin; Lee, Choongsze; Fu, Donglong; Agarwal, Ankur; Le, Thuy Thanh; Tsapatsis, Michael; Palmer, Jeremy C.; Weckhuysen, Bert M.; Dauenhauer, Paul J.; Zou, Xiaodong; et al. (Nature materials, 2020)
There is growing evidence for the advantages of synthesizing nanosized zeolites with markedly reduced internal diffusion limitations for enhanced performances in catalysis and adsorption. Producing zeolite crystals with sizes less than 100 nm, however, is non-trivial, often requires the use of complex organics and typically results in a small product yield. Here we present an alternative, facile approach to enhance the mass-transport properties of zeolites by the epitaxial growth of fin-like protrusions on seed crystals. We validate this generalizable methodology on two common zeolites and confirm that fins are in crystallographic registry with the underlying seeds, and that secondary growth does not impede access to the micropores. Molecular modelling and time-resolved titration experiments of finned zeolites probe internal diffusion and reveal substantial improvements in mass transport, consistent with catalytic tests of a model reaction, which show that these structures behave as pseudo-nanocrystals with sizes commensurate to that of the fin. This approach could be extended to the rational synthesis of other zeolite and aluminosilicate materials. Nanosized zeolites enable better catalytic performance; however, their synthesis is non-trivial. Here, a simple treatment is presented that enables the growth of nanosized fins on zeolites that act as pseudo-nanoparticles, reducing deactivation rates for methanol-to-hydrocarbon catalysis.